Dakwah Kelompok dalam Komunitas Pejuang Mahar - Titin Nurjanah; Uwes Fatoni (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2019)
This research is to study about da'wah in the community of dowry fighters. How is the process of preaching the dowry fighting community in influencing mad'u. This study uses qualitative methods with the methodology of feomenology. The technique of collecting data in this research is observation and interviews. This study uses the theory of trusted communication with the input process output method, namely by incorporating da'wah material into the target mad'u with the process of studies and then obtaining its output in the form of successful da'wah with a decision full of mad'u's confidence in emigrating. The theory makes the results of this study with the introduction of religious problems in the community, especially young men in courtship, which then held an approach to the reasons for the behavior of madu using the productivity of the dowry fighters community by motivating madu to solve the shari 'provisions. at Islam which then made the mad'u run according to what was suggested by the missionary community.AbstrakPenelitian ini mengkaji dakwah kelompok dalam komunitas pejuang mahar khususnya proses komunikasi dalam dakwah komunitas pejuang mahar untuk memotivasi jamaahnya menghindari pacaran. Penelitian ini menggunkan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dalam penelitin ini dengan obervasi dan wawancara.  Penelitian ini menggunakan teori komunikasi kelompok terpercaya dengan input-proses-output. Hasil penelitian ini menemukan alur pengenalan masalah keagamaan masyarakat terutama pemuda dalam maraknya pacaran. yaitu memasukan bahan dakwah ke dalam sasaran mad’u dengan proses kajian-kajian lalu mendapatkan outputnya berupa keberhasilan dakwah dengan keputusan penuh keyakinan mad’u dalam berhijrah. proses pendekatan dilakukan dengan melihat alasan dari prilaku mad’u. komunitas pejuang mahar memotivasi mad’u menemukan jalan keluar yang sesuai dengan ketentuan syari’at Islam.